Web-based system with parallel processing to optimize online catalog management at a technology company in Trujillo - Ramirez Gamarra, Gabriel Gonzalo; Sierra-Liñan, Fernando (LACCEI, 2025)
In the absence of an adequate technological solution, catalog management processes were manual and inefficient, making it difficult to consult and update them. To solve this problem, a web-based catalog management system optimized with parallel processing was implemented, with the aim of improving operational efficiency, data accuracy, and employee satisfaction. The study was applied, with a quantitative approach and pre-experimental design, and involved 32 employees directly involved in catalog management. Key indicators such as system response time, data update accuracy, operating cost reduction, and user satisfaction were evaluated. The results were highly positive: response time was reduced by 69.95%, data update accuracy improved by 20.25%, operating costs decreased by 32%, and user satisfaction increased by 97.93%. These advances reflect a notable improvement in efficiency, reliability, and workplace well-being. The agile Scrum methodology was essential for flexible and effective management, while validation with users and experts strengthened the usability and technical robustness of the system, surpassing results obtained in previous research.